Microbiological and formaldehyde analysis in beef jerky marketed in public markets in Recife/PE (Research, Society and Development, 2022)
The consumption of beef jerky is common in northeastern Brazil and its main form of commercialization and acquisition takes place in public markets. The objective of this work was to analyze the presence of formaldehyde and pathogenic microorganisms in jerked beef sold in public markets in the metropolitan region of Recife, Northeast Brazil. Twenty samples of beef jerky of different cuts were acquired from 10 stalls located in 3 public markets. The samples were sent to the laboratory to perform the formaldehyde test and microbiological analysis. It was found that 40% of the samples had formaldehyde and 100% of the samples were outside the standard allowed by IN nº 60 (Brasil, 2019), of the National Health Surveillance Agency. There is a need for the presence of public policies and inspection actions, aiming at improving the conditions of exposure and storage in the boxes to guarantee the food safety of the food sold.